2012
DOI: 10.1039/c2ee02485c
|View full text |Cite
|
Sign up to set email alerts
|

Structure and decomposition of zinc borohydride ammonia adduct: towards a pure hydrogen release

Abstract: Zn(BH 4) 2 •2NH 3 , a new ammine metal borohydride, has been synthesized via simply ball-milling a mixture of ZnCl 2 •2NH 3 /2LiBH 4. Structure analysis shows that the subsequent complex has a monoclinic structure with unit-cell parameters of a = 6.392(4) Å, b = 8.417(6) Å, c = 6.388(4) Å and β = 92.407(4) ° and space group P2 1 , in which Zn atoms coordinate with two BH 4 groups and two NH 3 groups. The interatomic distances reported herein show that Zn-H bonding in Zn(BH 4) 2 •2NH 3 is shorter than Ca-H bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
95
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 56 publications
4
95
0
Order By: Relevance
“…[36][37][38][39] Interestingly,d estabilization is observed for most metal borohydrides with low electronegativity (c p <~1.6), whereas metal borohydrides with ah igh electronegativity (c p >~1.6) are stabilized by NH 3 (i.e.,they releaseg as at higher temperatures). [4,15] However, the generalm echanism for decomposition is not fully understood.…”
Section: Mechanism For the Decomposition Of Ammine Metal Borohydridesmentioning
confidence: 92%
“…[36][37][38][39] Interestingly,d estabilization is observed for most metal borohydrides with low electronegativity (c p <~1.6), whereas metal borohydrides with ah igh electronegativity (c p >~1.6) are stabilized by NH 3 (i.e.,they releaseg as at higher temperatures). [4,15] However, the generalm echanism for decomposition is not fully understood.…”
Section: Mechanism For the Decomposition Of Ammine Metal Borohydridesmentioning
confidence: 92%
“…Thus the latter are often more thermally stable than their respective metal borohydride [104,130]. The stabilization may be due to complex formation and a shielding effect of the metal cation, which would otherwise be reduced to the metallic state, e.g., Zn(BH 4 ) 2 ·4NH 3 and Zn(BH 4 ) 2 ·2NH 3 [135]. Previously, a low NH 3 /BH 4 − ratio (n/m~1) and strong dihydrogen bonds were assumed to provide H 2 rich (and NH 3 poor) gas release during thermolysis.…”
Section: Metal Borohydrides Modified By Neutral Moleculesmentioning
confidence: 99%
“…The most extensive series of crystalline ammine metal borohydride is formed by Y(BH 4 ) 3 ·nNH 3 (n = 1, 2, 4, 5, 6 and 7), which illustrates the great structural flexibility ranging from cation complexes (n = 6 and 7), molecular neutral complexes (n = 4 and 5), one-dimensional chain like (n = 2), and two-dimensional layered structure (n = 1) [132]. Ammine metal borohydrides have been considered promising hydrogen storage materials, e.g., Al(BH 4 ) 3 ·6NH 3 , Li 2 Al(BH 4 ) 5 ·6NH 3 , and Zn(BH 4 ) 2 ·2NH 3 release 9 to 12 wt % H 2 in the temperature range 115 to 170 • C with traces of NH 3 [133][134][135].…”
Section: Metal Borohydrides Modified By Neutral Moleculesmentioning
confidence: 99%
“…12 In recent years, various studies have found that these metal borohydrides typically demonstrate improved hydrogen storage properties when complexed with ammonia, forming a new class of materials called metal borohydride ammoniates (MBAs). [13][14][15][16][17][18] Generally, MBAs tend to release hydrogen gas at more practical temperatures and greater purity than their plain MB counterparts. 13 Furthermore, recent experiments have mixed various MBAs with MBs or ammonia borane (NH 3 BH 3 ) to tune the H 2 release temperature and purity.…”
Section: Introductionmentioning
confidence: 99%